The Girl with the Dragon Tattoo: Millennium #1 - Larsson, Stieg, 1954-2004; Vance, Simon; Random House Audio Publishing (New York : Random House Audio, 2008)
Harriet Vanger, a young scion of one of Sweden's wealthiest families, disappeared forty years ago, and now her octogenarian uncle wants to know the truth about what he believes was her murder. He hires a crusading journalist and his tattooed hacker genius assistant, and they discover astonishing corruption and an unexpected connection to themselves.
The first book in the Millennium series.
Sequel: The girl who played with fire.
Compact discs.
Originally published: Stockholm : Norstedt, 2005.
Read by Simon Vance.
Keywords: Larsson, Stieg, -- 1954-2004 -- Translations into English; Blomkvist, Mikael (Fictitious character) -- Fiction; Salander, Lisbeth (Fictitious character) -- Fiction; Disappeared persons -- Fiction; Computer hackers -- Fiction; Journalists -- Fiction; Rich people -- Fiction; Uncles -- Fiction; Stockholm (Sweden) -- Fiction; Mystery fiction; Swedish fiction -- 21st century -- Translations into English; Audiobooks on CD